PEMBELAJARAN MATEMATIKA TERPADU PADA ANAK USIA DINI - Ulfa Maulida; Riska Yuliani; Ira Anggraeni (LPPM Universitas Bina Bangsa, 2022)
This paper aims to analyze integrated mathematics learning in early childhood education. Education for early childhood is one of the processes of growth and development that has a unique nature so that it has growth and development that is in accordance with the needs of the level of growth and development. This article is based on the assumption that early childhood should not be taught to count. Researchers used a meta-analysis of previous research and literature on mathematics learning in early childhood education. The findings from this article are expected to have a positive impact on the growth and development of early childhood. It is also hoped that learning mathematics in early childhood can be carried out with concepts that are truly in accordance with the characteristics of early childhood learning